2019
DOI: 10.1111/jan.14204
|View full text |Cite
|
Sign up to set email alerts
|

Flying by the seat of their pants: A grounded theory of school nurse case management

Abstract: Aims To develop a theory describing the processes and actions involved with school nurse case management for school‐aged children with chronic conditions in the K12 system. Design Case management is an essential practice for the school nurse. Little is known about actual case management practice in real‐world settings. Grounded theory methodology following a literature‐based conceptual model of school nurse case management. Methods A purposive maximum variation sampling was used for data collection and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In four articles, nurses recognized that there was insufficient school nurse staffing to support children (Kao et al, 2018; Liberatos et al, 2013; Seki et al, 2017; Svavarsdottir et al, 2013). In five articles, they reported a lack of staff education (Kao et al, 2018; Terry & Trott, 2019) or training (Klein & Evans‐Agnew, 2019; March et al, 2020; Marshall et al, 2013). Recently, school nurses have been required to be skilled with modern devices and receive increased training (March et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In four articles, nurses recognized that there was insufficient school nurse staffing to support children (Kao et al, 2018; Liberatos et al, 2013; Seki et al, 2017; Svavarsdottir et al, 2013). In five articles, they reported a lack of staff education (Kao et al, 2018; Terry & Trott, 2019) or training (Klein & Evans‐Agnew, 2019; March et al, 2020; Marshall et al, 2013). Recently, school nurses have been required to be skilled with modern devices and receive increased training (March et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that a lack of evidence‐based guidance and variations in best practices were barriers in providing necessary support to children (Marshall et al, 2013). Typically, school nurses take on multiple roles, which leads to the imperfect care practice (Klein & Evans‐Agnew, 2019). Additionally, they experienced difficulties related to variations in school staff support and inconsistent classroom practices in caring for students requiring the use of modern medical devices (March et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are limited scholarly articles specific to SNCM, Bachman et al (2015) note that school nurses are considered providers of care coordination and case management services including supports within a broad range of providers and systems. In addition, research by Klein and Evans-Agnew (2019) indicate that despite contextual constraints, such as high caseloads and limited hours, school nurses are attempting to do case management.…”
Section: Case Managementmentioning
confidence: 99%
“…The practice component of health promotion is part of the principal of community/public health (community/public health principle). All principles of the Framework were used to address the barriers identified by Washington state school nurses (Klein & Evans-Agnew, 2019; NASN, 2016a).…”
Section: Implications For School Nursing Practicementioning
confidence: 99%